PENGARUH PENGGUNAAN SISTEM AKUNTANSI TERKOMPUTERISASI DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN PERPAJAKAN UMKM DI KOTA TANGERANG SELATAN - Fadilah Rizky Ramadhan; Dani Rahman Hakim (Journal of Research and Publication Innovation, 2026)
This study examines the influence of computerized accounting systems and tax socialization on MSME tax compliance in South Tangerang City. A quantitative method was applied using 105 MSME respondents selected through incidental sampling. Data were analyzed using PLS-SEM with SmartPLS. The results show that the use of computerized accounting systems falls into the moderate category, while tax socialization and tax compliance are in the fairly high category. Structural analysis confirms that computerized accounting and tax socialization have a positive and significant effect on MSME tax compliance. These findings highlight the importance of digital accounting literacy and stronger tax outreach in improving tax compliance.